(untitled) (Research, Society and Development, 2022)
Introduction: Sleep is essential for maintaining the general health of professional athletes. Poor sleep quality is caused by sleep disturbances, training schedule, irregular sleep habits, overtraining and reduced amount of sleep interfering with the athlete’s recovery. Objective: To investigate the sleep quality of athletes in different sports and associated factors. Methodology: Integrative literature review through searches in electronic databases MEDLINE, SCIELO, BVS and LILACS, by combination of descriptors. Studies published in full, available online in the last 10 years, in Portuguese and English on the research topic, were included. Seven studies were included, most of them cross-sectional observational and one descriptive study, with the participation of athletes of both sexes. Results: It was found that professional athletes have poor sleep quality related to the training schedule and emotional state during the competition period (nervousness, anxiety) that lead to insomnia, night awakenings, pain during sleep. Conclusion: There was evidence that the magnitude of the sleep quality of athletes plays an important role in their physical performance and performance in their daily lives. Strategies to optimize athletes’ sleep are needed to improve sleep quantity and quality.